Family management, corporate governance and firm risk - Cham, Justin Dao Yong (Nanyang Technological University, 2010)
The purpose of this study is to examine the effect of family management on a firm’s total risk in Singapore’s context. Specifically, the study will look into the effects of the proportion of family members, existence of an independent chairman and board vigilance on a firm’s total risk. Interactions between these factors are also examined in the paper. We found that a firm’s total risk is on average, negatively affected by the proportion of family members on the board and board vigilance. In addition, we found that the negative association between the proportion of family members and total risk is stronger under conditions of high board vigilance.